Danger-- icebergs! - Gans, Roma, 1894-; Rosenblum, Richard (New York : Harper & Row, 1987)
Explains how icebergs are formed from glaciers, move into the ocean, create hazards to ships, and melt away.
Previous edition: Icebergs, 1964.
Wilson's Children
Elem. School Library Collection
School Library Journal
2.9
K-3
Keywords: Icebergs -- Juvenile literature; Icebergs; Icebergs